The role of driving force-pressure-state-impact-response(DPSIR) framework on Penang National Park - Hong , Chern Wern; Chan , Ngai Weng (Environmental Management Society, Malaysia, 2011)
The Penang National Park (PNP), previously known as Pantai Acheh forest, is one of the few remaining natural heritages in Northern Peninsular Malaysia, Although THe PNP is not a virgin forest as timber extraction has been carried out in the 1910s to 1930s, it still has unique features, which include ameromictic lake, wetlands, magroves, mudflats, coral reefs, turtle nesting sanctuary, sandy beaches and pristine seas. These beatiful flora and fauna must be preserved and sustained for future generations.Driving Force-Pressure-State-Impact-Response(DPSIR) framwork is executed on the PNP and its impactson ecosystems. DPSIR is flexible as it allows policy-makers to understand more easily the environmental problems of the park. However, the framework must include a robust methodology to facilitate the measurement of key indicatore of governance and performance, and to focus on outcomes rather than on the processes.